By the Honorable Thomas Fitch, Esq ; governor of His Majesty's English colony of Connecticut ... A proclamation for a day of public fasting and prayer : ... Wednesday, the eleventh day of April next ... Given under my hand at the Council-chamber at Hartford, the ninth day of March ... 1764 (Printed by Timothy Green, printer to the governor and Co., 1764)
March 9, 1764 broadside issued by Governor Thomas Fitch of Connecticut, proclaiming April 11th as a day of public fasting and prayer in light of unexpected hostilities from the Indians.